2014
DOI: 10.1038/srep04964
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized charge oscillations in correlated electron systems

Abstract: Strongly correlated phases exhibit collective carrier dynamics that if properly harnessed can enable novel functionalities and applications. In this article, we investigate the phenomenon of electrical oscillations in a prototypical MIT system, vanadium dioxide (VO2). We show that the key to such oscillatory behaviour is the ability to induce and stabilize a non-hysteretic and spontaneously reversible phase transition using a negative feedback mechanism. Further, we investigate the synchronization and coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
131
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(141 citation statements)
references
References 40 publications
1
131
0
Order By: Relevance
“…Discrete-component implementations of these VO 2 -based oscillators have been realized in the laboratory [11]. First attempts to couple and synchronize more VO 2 oscillators are currently under investigation [1], [13]. However, similarly to what has been done for MOSFET devices, as the VO 2 -based manufacturing process gets more mature, it becomes more apparent the need for developing circuit-level models of the new physical devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discrete-component implementations of these VO 2 -based oscillators have been realized in the laboratory [11]. First attempts to couple and synchronize more VO 2 oscillators are currently under investigation [1], [13]. However, similarly to what has been done for MOSFET devices, as the VO 2 -based manufacturing process gets more mature, it becomes more apparent the need for developing circuit-level models of the new physical devices.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, a great research effort has been spent in developing new fabrication processes, alternative to conventional CMOS, and targeted at the realization of compact and easy scalable nano-oscillators [1]- [3]. Such emerging technologies are expected to soon allow the large-scale integration of array of coupled oscillators paving the way to novel applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that connecting a VO 2 device with a resistor and a capacitor, of proper resistance and capacitance values, it is possible to fabricate very compact relaxation nano-oscillators [2]. The simple fabrication flow, the easy scalability with the possibility to achieve high packaging density, make VO 2 nano-oscillators promising candidates to integrate a large array of coupled oscillators for bio-inspired neurocomputing [2,3].…”
mentioning
confidence: 99%
“…Recently, it has been shown that connecting a VO 2 device with a resistor and a capacitor, of proper resistance and capacitance values, it is possible to fabricate very compact relaxation nano-oscillators [2]. The simple fabrication flow, the easy scalability with the possibility to achieve high packaging density, make VO 2 nano-oscillators promising candidates to integrate a large array of coupled oscillators for bio-inspired neurocomputing [2,3].However, electrical measurements reveal that the switching-like behaviour of a two-terminal VO 2 comes at the expense of a hysteresis with the IMT and the MIT transition being driven by two different critical electric field values. In this Letter, we provide, for the first time, a circuit-level model of the hysteresis mechanism which is a key to predicting and controlling the dynamics of relaxation oscillators built on VO 2 devices.…”
mentioning
confidence: 99%
“…[20][21][22][23][24] In this letter we present our results on the (non-constant resistive) coupling of two self-sustained van der Pol oscillators via a memristive device. [2,[25][26][27][28] In this feasibility study we demonstrate an autonomous phase and frequency locking of the two oscillators (i.e. a transition from the asynchronous to a remnant synchronous state) due to the pulse dependent memristive coupling.…”
mentioning
confidence: 99%